1985
DOI: 10.2527/jas1985.6151178x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Vomitoxin and Feed Intake on the Performance and Blood Characteristics of Young Pigs

Abstract: Thirty barrows (average weight 8.4 kg) were used in a 3-wk experiment to determine the effects of the ingestion of vomitoxin (deoxynivalenol)-contaminated feed on performance and blood chemistry. The barrows were assigned randomly to consume either: 1) a control diet (C), fed ad libitum, 2) a vomitoxin contaminated diet (V; 10.5 ppm), fed ad libitum, or 3) a vomitoxin contaminated pair-fed at levels equal to those consumed by V animals (PF). The V and PF pigs had similar daily gains (.19 vs .20 kg) and feed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 10 publications
4
15
2
Order By: Relevance
“…2, lower DON levels resulted in negligible feed intake effects after the initial exposure period. These results are consistent with earlier reports, where feed intake was often restored after 7 to 14 d if diets contained less than 3 mg/kg DON (Lun et al, 1985;Grosjean et al, 2002;Rempe et al, 2013). These observations also support the hypothesis that pigs develop some degree of adaptation to DON after the initial exposure period (Dersjant-Li et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…2, lower DON levels resulted in negligible feed intake effects after the initial exposure period. These results are consistent with earlier reports, where feed intake was often restored after 7 to 14 d if diets contained less than 3 mg/kg DON (Lun et al, 1985;Grosjean et al, 2002;Rempe et al, 2013). These observations also support the hypothesis that pigs develop some degree of adaptation to DON after the initial exposure period (Dersjant-Li et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies showed increased serum chloride in rats given 0.25À1.0 mg/kg bw deoxynivalenol (2.5À10 μg/g in diet), 17 and lower serum calcium and phosphorus in pigs fed 10 μg of deoxynivalenol/g in diet compared with controls, 20 but elevated serum calcium and magnesium were found in rats fed fumonisin B1 (7.5 μg/g), whereas serum chloride, phosphate, and ALP were not altered by fumonisin B1. 16 In our experiment, significant increases of serum chloride and decreases of serum phosphorus and magnesium were found in rats fed the mixture of three mycotoxins, which may be a sign of nephrotoxicity, because a Different letters in individual columns indicate significant difference for different sex (lower case letter for male and capital letter for female, p < 0.05).…”
Section: Articlementioning
confidence: 94%
“…Although there is limited evidence that feed conversion may be redltced in pigs fed diets containing more than 8 mg DON kg-' (Blaney and Williams 1991), most previous studies have indicated that the effect of DON on BW is indirect and due to a reduction in feed acceptability and intake (Lun et al 1985;Chavez and Rheaume 1986) xBW is body weight. wSee Table 3 for explanation.…”
Section: Animals and Housingmentioning
confidence: 99%